Neurologic impairment in Wilson disease - Dusek, Petr; Litwin, Tomasz; Członkowska, Anna (Annals of translational medicine, 2019)
Neurologic symptoms in Wilson disease (WD) appear at an older age compared to hepatic symptoms and manifest in patients with misdiagnosed liver disease, in patients when the hepatic stage is clinically silent, in the case of non-compliance with anti-copper treatment, or with treatment failure. Neurologic symptoms in WD are caused by nervous tissue damage that is primarily a consequence of extrahepatic copper toxicity. Copper levels in brain tissues as well as cerebrospinal fluid (CSF) are diffusely increased by a factor of 10 and its toxicity involves various mechanisms such as mitochondrial toxicity, oxidative stress, cell membrane damage, crosslinking of DNA, and inhibition of enzymes. Excess copper is initially taken-up and buffered by astrocytes and oligodendrocytes but ultimately causes dysfunction of blood-brain-barrier and demyelination. Most severe neuropathologic abnormalities, including tissue rarefaction, reactive astrogliosis, myelin palor, and presence of iron-laden macrophages, are typically present in the putamen while other basal ganglia, thalami, and brainstem are usually less affected. The most common neurologic symptoms of WD are movement disorders including tremor, dystonia, parkinsonism, ataxia and chorea which are associated with dysphagia, dysarthria and drooling. Patients usually manifest with various combinations of these symptoms while purely monosymptomatic presentation is rare. Neurologic symptoms are largely reversible with anti-copper treatment, but a significant number of patients are left with residual impairment. The approach for symptomatic treatment in WD is based on guidelines for management of common movement disorders. The vast majority of WD patients with neurologic symptoms have abnormalities on brain magnetic resonance imaging (MRI). Pathologic MRI changes include T2 hyperintensities in the basal ganglia, thalami and white matter, T2 hypointensities in the basal ganglia, and atrophy. Most importantly, brain damage and neurologic symptoms can be prevented with an early initiation of anti-copper treatment. Introducing population WD screening, e.g., by exome sequencing genetic methods, would allow early treatment and decrease the neurologic burden of WD.
Keywords: magnetic resonance imaging (MRI); neuroradiology; neuropathology; Wilson disease (WD); copper toxicity; clinical scales